Pengaruh Pendapatan, Financial Attitude, Financial Knowledge, Self-Efficiancy, dan Self-Control Terhadap Financial Behaviour Generasi Sandwich di Kota Mataram - Amalia, Ainayya; Sasanti, Elin Erlina (Jurnal Riset Mahasiswa Akuntansi, 2024)
This study aims to empirically test the level of income, financial attitude, financial knowledge, financial self-efficacy, and self-control on the financial behaviour of the sandwich generation in Mataram City. This research is an associative research with a quantitative approach. The population in this study is the sandwich generation in Mataram City. The sample in this study was determined using non probability sampling with the Lemeshow formula, resulting in a research sample of 96. This study uses primary data obtained by distributing questionnaires to respondents, then processing the data using data analysis tools in Partial Least Square (PLS) version 4. The results of this study are financial self-efficacy and self-control have a positive effect on the financial behavior of the sandwich generation in Mataram City. Meanwhile, income level, financial attitude, and financial knowledge have no effect on financial behaviour.